2017
DOI: 10.1177/000313481708300844
|View full text |Cite
|
Sign up to set email alerts
|

Chest Tube Removal in Simple Pneumothorax: Does Water-Seal Duration Matter?

Abstract: Timing of chest tube (CT) removal after transition from suction to water-seal (WS) varies when treating traumatic simple pneumothoraces (PTXs). Longer periods of WS may identify slow-occurring PTXs reducing CT replacement, whereas shorter periods may expedite patient disposition and have associated cost savings. Prior studies support the need for an interval of WS. We compare durations of WS, looking at rates of CT reinsertion. A 10-year retrospective review on trauma patients with a simple PTX requiring a CT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In 1994 Davis et al [ 32 ] compared continuing suction with a short period of water seal before removal of the chest tube, and found that continuing suction until chest tube removal reduced total chest tube duration and required shorter time to remove the chest tube following air leak resolution. In contrast, Martino et al and Bridges et al, found no difference between continuing suction and a short water seal in chest tube duration or hospital length of stay between suction or a short water seal before chest tube removal [ 33 , 34 ]. Because the results from these studies are contradictory, it is hard to give a firm recommendation for the management just before drain removal.…”
Section: Discussionmentioning
confidence: 99%
“…In 1994 Davis et al [ 32 ] compared continuing suction with a short period of water seal before removal of the chest tube, and found that continuing suction until chest tube removal reduced total chest tube duration and required shorter time to remove the chest tube following air leak resolution. In contrast, Martino et al and Bridges et al, found no difference between continuing suction and a short water seal in chest tube duration or hospital length of stay between suction or a short water seal before chest tube removal [ 33 , 34 ]. Because the results from these studies are contradictory, it is hard to give a firm recommendation for the management just before drain removal.…”
Section: Discussionmentioning
confidence: 99%
“…As noted by Bridges et al, using a short interval of water seal can reduce the time of TT by almost a day as well as reduce costs and decrease hospital LOS. 8 Mao et al points out that increased duration of water seal can show increased hospital length of stay and increase number of chest radiographs. 5 Also, some institutions utilize high-flow oxygen for the "nitrogen washout" effect to facilitate complete resolution of the pneumothorax.…”
Section: Discussionmentioning
confidence: 99%